Prevalence of diabetic comorbidities and knowledge and practices of foot care among diabetic patients: a cross-sectional study - Abdulghani HM (Dove Medical Press, 2018)
Hamza Mohammad Abdulghani,1 Areej Salman AlRajeh,2 Budoor Hussain AlSalman,2 Lulwah Sami AlTurki,2 Norah Sulaiman AlNajashi,2 Mohammad Irshad,2 Khalid Hamad Alharbi,3 Yazeed Eid AlBalawi,3 Yazeed A AlSuliman,3 Tauseef Ahmad2 1Department of Medical Education, College of Medicine, King Saud University, 2College of Medicine, King Saud University, 3King Khalid University Hospital, King Saud University, Riyadh, Saudi Arabia Background: Diabetes mellitus with comorbid complications constitute a major public health problem worldwide. The aim of this study was to evaluate the risk of comorbid complications with glycosylated hemoglobin levels and diabetes duration. Also assessed were patients’ diabetic foot-care knowledge and practices. Patients and methods: This was a quasiexperimental study. A total of 360 type 2 diabetes mellitus patients were interviewed at a government health care center in Riyadh, Saudi Arabia. Diabetic complications and HbA1c-level data were collected from hospital records. A standard questionnaire was used to assess their diabetic foot-care knowledge and practice. Results: Of the type 2 diabetes mellitus patients, 32.5% had highly uncontrolled glycosylated hemoglobin (HbA1c) levels (≥8.6%) and 62.8% had had diabetes >10 years. The patients had comorbid complications, such as hypertension (61.4%), dyslipidemia (58.6%), retinopathy (23.3%), heart disease (14.4%), and severe foot complications (3.9%). The majority of highly uncontrolled HbA1c-level patients had retinopathy (OR 8.90, P=0.0001), foot complications (OR 8.09, P=0.0001), dyslipidemia (OR 2.81, P=0.010), and hypertension (OR 2.0, P=0.028) compared to the controlled HbA1c-level (<7%) group. Patients with diabetes >10 years also had higher prevalence of foot complications (OR 2.92, P=0.0001), retinopathy (OR 2.17, P=0.011), and hypertension (OR 1.67, P=0.033). From patient responses, physicians examined only 34.2% of patient feet and 36.7% of patients received physicians advice for foot care. About 70% of patients had knowledge of diabetic foot care; however, only 41.7% of patients always examined their feet, 41.4% washed feet with warm water, 31.4% carefully dried between the toes, and 33.1% were using foot-moisturizing substances. Conclusion: The prevalence of comorbid complications was higher in the Saudi population compared to other international studies. Also, foot-care practice was not satisfactory. Therefore, there is need of improvement and increased awareness among physicians and patients to check regularly for proper care of the diabetic foot to avoid diabetic foot-related complications. Keywords: diabetic mellitus, comorbid complication, foot care, Saudi Arabia